Discursive forms of the Peruvian popular press in the 90s - Torres Vitolas, Miguel Ángel (2022)
In the nineties, popular press (also called prensa chicha) became in Peru an important presence in the communication sphere. During this period, this presence was linked to relations of clientelism and subordination formed with Fujimori’s government. Nevertheless, this presence remains important after all these years, even after many changes in government. Our research looks to describe from a semiotic perspective those enunciative characteristics forged and consolidated during that period. Our research aims to outline a description of enunciative strategies more than a content analysis, in order to establish the configuration of the reading contract in this press. We have followed a semiotic approach of enunciation understanding it as a representation: a represented enunciation. Through the analysis of the most read journals in this period (Ojo, Extra, and Ajá), we have established the textual tipologies faced by the reader and forms of enunciation presented in those texts. Our research has recognized the consolidated presence of some textual genres: the gossip column in the sports and showbiz sections, and a growing presence of the interview.